Postcard from "Nick" to Éamonn Ceannt concerning a piper's "loyalty" - Ceannt, Éamonn, 1881-1916 (1904)
Postcard from "Nick" to E.T. Kent enquiring after details of a piper named Flanagan, in particular his "loyalty", as he is due to play at the upcoming St. Patrick's Day concert and the [Gaelic League] are "much perturbed". Written on a Gaelic League postcard advertising the aforementioned concert. Includes an illustration entitled 'The second coming of St. Patrick', showing Patrick quashing serpents named 'Pseudo Irish concerts', 'stage Irishmen' and 'West Britonism'.
Keywords: Ceannt, Éamonn, -- 1881-1916 -- Correspondence; Gaelic League (Ireland); Pipe (Musical instrument); Folk music -- Ireland; Ireland -- History -- 1901-1910